Quantum Imaging in Medical Diagnostics: The Future of Non-Invasive Precision Medicine - Hassan, Zainab Mohaisen Oleiwi; Ali, Zahraa Ali Obaid; Muslim, Abbas Nasir Shanshul; Hashim, Dhafer Talib Fawari (American Journal of Botany and Bioengineering, 2025)
Medical imaging plays a crucial role in diagnostics, guiding both invasive and non-invasive medical procedures. Since the invention of the X-ray method in 1895, numerous medical imaging techniques have been developed, including widely used technologies like CT, MRI, ultrasound, and PET scans. Contemporary medical imaging relies heavily on electromagnetic radiation in the range of 10^−14−10^−1 m, which carries information about structures and phenomena in the human body. Quantum technologies, particularly quantum-enhanced imaging techniques, can improve the state-of-the-art performance of a few sub-technologies of MRI tailored for medical applications. In recent years, the number of publications on quantum imaging, sensing, and metrology has increased significantly, demonstrating the high interest in this research area and the applications prepared in different fields. The emergence of quantum imaging technology holds promises for various applications, bringing advanced techniques for imaging improvement and patient safety. Traditional imaging techniques encounter a resolution limit of the involved light, making it impossible for the imaging devices to utilize the light sub-wavelength. The performance of non-invasive imaging using nurse diagnosis is limited due to the sophistic frequencies of heart and lung sounds employed. Proper spectral analysis techniques can be used to detect the respiratory rhythm of adults of various ages, frequency and transesophageal cardiac cycles, and global brain oscillations of elderly patients. Quantum optics enters another level on top of these classical optical techniques. Using entangled photons for imaging has obvious advantages as entanglement is known for connectivity. Health outcomes can be improved through quantum-enhanced medical imaging for non-invasive precision medicine.